Relationship between different types of complement syntax and false belief in Mandarin-speaking children with autism spectrum disorder and typically developing children - Guo, Qiang; Pan, Qianqian; Liu, Qiaoyun; Wang, Tingzhao; Cao, Shuqin; Lin, Yunqiang; Hu, Bisheng (Frontiers in Psychology, 2022)
Previous studies have shown that complement syntax is closely associated with false belief (FB) in children with autism spectrum disorder (ASD). However, the relationship between different types of complement syntax and FB remains unclear. This study examined the relationship between different types of complement syntax and FB in both ASD and typically developing (TD) children. Thirty Mandarin-speaking ASD and TD children, each matched for language ability, were included. Children completed different types of complement syntax tasks, verbal and nonverbal FB. For the ASD children, results demonstrated that sentential complement syntax independently predicted verbal and nonverbal FB, while phrasal complement syntax only predicted nonverbal FB. For the TD children group, sentential complement syntax only predicted verbal FB. This indicates that as the language demands of the FB task decrease, ASD children can use both types of complement syntax for its prediction. Moreover, the characteristics of ASD children differ from TD children in terms of the relationship between different types of complement syntax and FB. The results of this study support de Villiers' point of view from the Mandarin perspective and provide evidence for the social-cognitive component of the theory of mind.